Innentitelbild: Edge‐to‐Center Propagation of Photochemical Reaction during Single‐Crystal‐to‐Single‐Crystal Photomechanical Transformation of 2, 5‐Distyrylpyrazine Crystals (Angew. Chem. 52/2022). (14th December 2022) - Morimoto, Kohei; Kitagawa, Daichi; Sotome, Hikaru; Ito, Syoji; Miyasaka, Hiroshi; Kobatake, Seiya
Abstract : Photochemical reaction of 2, 5‐distyrylpyrazine single crystals was investigated by Daichi Kitagawa, Seiya Kobatake, and co‐workers in their Research Article (e202212290) . Under uniform illumination conditions, the photochemical reaction started from the edge of the crystals and propagated to the center. Both surface and cooperative effects are shown to be essential for the edge‐to‐center propagation of the photochemical reaction.